Effects of forsythin extract in Forsythia leaves on intestinal microbiota and short-chain fatty acids in rats fed a high-fat diet - Lanlan Gui; Shaokang Wang; Jing Wang; Wang Liao; Zitong Chen; Da Pan; Hui Xia; Guiju Sun; Su Tian (Food Science and Human Wellness)
Forsythia suspensa, belonging to the deciduous shrubs of the Luteaceae family, a traditional Chinese medicine, has effects of alleviating swelling, clearing heat, detoxification and promoting blood circulation. The leaves of F. suspensa contain multiple chemical components and have a long history of use in folk medicines and health foods. The purpose of this study was to explore the effects of forsythin extract from F. suspensa leaves on intestinal microbiota and short-chain fatty acid (SCFA) content in rats with obesity induced by a high-fat diet. Forsythin extract in F. suspensa leaves increased the abundance of the intestinal microbiota, ameliorated intestinal microbiota disorders and inhibited the increase in total SCFA content in the intestinal tract in rats with obesity induced by a high-fat diet. These results suggested that forsythin extract in F. suspensa leaves may slow the development of obesity induced by a high-fat diet; thus, its active components and efficacy are worthy of further study.